The influence of big five personality traits on social entrepreneurship start up intentions among local community in Kelantan - Wan Fariza Azima Che Azman (2019)
Past researchers merely focused on commercial entrepreneurship with an emphasis of financial returns over social returns. As a result, many global financial scandals happen such as Enron and WorldCom. The sheers impact also spread in companies all over the countries which shows that commercial entrepreneurs pursue their opportunities in the short – term regardless of social entrepreneurs that are more focus on social welfare that might benefited for the long time. Therefore, time has come for entrepreneurs to swift towards an integrate perspectives viewpoint of business model that includes the mixture of economy, social and environmental values. Social entrepreneurship is making profit through selling by to the consumer base. The intentions of social entrepreneurship agents would help out in clear understanding of social entrepreneurship since they are the ones who embrace the activity. In this sense, this article aims to examine the relationship between Big Five personality traits and social entrepreneurship start up intentions. The research variables were Big Five personality traits (agreeableness, extroversion, neuroticism, openness and conscientiousness) and social entrepreneurship start up intentions (social vision, financial return, innovation, sustainability and social networks). Quantitative research method was used and data were collected by distributing survey questionnaires to the targeted respondents. 150 copies of questionnaires were administered to the local community in Kelantan, but a total of 104 were analyzed. The findings indicated that the Big Five personality traits (agreeableness, extroversion, neuroticism, openness and conscientiousness) has influenced social entrepreneurship start up intentions (social vision, financial return, innovation, sustainability and social networks). The outcome of this study revealed that there is a significance relationship between Big Five personality traits (agreeableness, extroversion, neuroticism, openness and conscientiousness) and social entrepreneurship start up intentions (social vision, financial return, innovation, sustainability and social networks). Hence, it is crucial to look thoroughly on Big Five personality traits and social entrepreneurship start up intentions so that the existing and future successful social entrepreneurs in the Malaysia can be born. Ultimately, it leads to the accomplishment of MED Malaysia as the entrepreneur one stop center. The government should encourage more Social Entrepreneurship (SE) business model to be developed with consequently more absolute plan in order to establish towards more dynamic economic environment.